2010
DOI: 10.1111/j.1749-7345.2010.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alternative Dietary Lipid Sources on Growth Performance and Fatty Acid Composition of Beluga Sturgeon, Huso huso, Juveniles

Abstract: The main aim of this investigation was to determine the impact of a total dietary fish oil (FO) replacement by vegetable oils (soybean [SO] and canola [CO] oil) on the growth and fatty acid (FA) composition of juvenile Beluga sturgeon, Huso huso. Three practical‐type diets with equal protein and lipid content were formulated using FO, SO, and CO. Each of the diets was fed to apparent satiation five times daily to H. huso (initial weight 206 ± 7.3 g) for 120 d. All groups grew equally well. Fish weight gain, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 62 publications
14
41
0
Order By: Relevance
“…Wild fish ova neutral lipids can have significantly lower proportions of total PUFAs compared to farmed fish (A. transmontanus, A. fulvescens) [6] and this is due to the higher quality of linolenic acid (18:3n-3) in diet of the farmed fish. Similar results have also been reported in cultured stellate sturgeon (A. stellatus) in Romania [2] and in other studies of cultivated beluga fatty acid composition of muscle tissue [33].Home viscous adaptation in response to environmental temperature is a primary reason for the prominence of n-3 PUFAs in the tissues of poikilotherms such as marine fish [34]. In current study, the cultivated beluga were cultured at 19ºC in freshwater for nine years and fed a plant oil containing diet.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…Wild fish ova neutral lipids can have significantly lower proportions of total PUFAs compared to farmed fish (A. transmontanus, A. fulvescens) [6] and this is due to the higher quality of linolenic acid (18:3n-3) in diet of the farmed fish. Similar results have also been reported in cultured stellate sturgeon (A. stellatus) in Romania [2] and in other studies of cultivated beluga fatty acid composition of muscle tissue [33].Home viscous adaptation in response to environmental temperature is a primary reason for the prominence of n-3 PUFAs in the tissues of poikilotherms such as marine fish [34]. In current study, the cultivated beluga were cultured at 19ºC in freshwater for nine years and fed a plant oil containing diet.…”
supporting
confidence: 87%
“…Others have reported that 18:1n-9 is the most common fatty acid in sturgeon and other fish eggs and tissues [6,26,[29][30][31][32][33]. The results of this study show that MUFAs were higher in wild than in domestic beluga.…”
Section: Fatty Acid Profile Chemical Composition and Fertilization Rsupporting
confidence: 46%
See 2 more Smart Citations
“…Interestingly, in this research the maximum level of RPC inclusion in sturgeon diet was 53 % and at this level the dietary protein was almost completely RPC protein. Even if we decided to not analyze productive results, we interestingly observed that the specific growth rate (SGR) was 5 times better than the case of white sturgeon (A. transmontanus) (Gawlicka et al, 2002), and the productive parameters were also better than Beluga sturgeon (Hosseini et al, 2010;Ta'ati et al, 2011), "AL" hybrid sturgeon , hybrid sturgeon (Acipenser schrenckii x Huso dauricus) (Qiyou X. et al, 2011) and white sturgeon (Lin et al, 1997).…”
Section: Discussion Diets and Fish Growthmentioning
confidence: 98%